Adult Bladder Exstrophy Managed by Complete Primary Repair: A Case Report - Deepak Mane; Shiva Singh; Vikram P Satav; Vilas P Sabale (Journal of Clinical and Diagnostic Research)
Bladder Exstrophic diseases, referred to collectively as Bladder Exstrophy-Epispadiasis complex, are a spectrum of embryological anomalies with a rare prevalence of approximately 3.3 per 1,00,000 live births with a male gender predominance. An 18-year-old man presented to Urology Outpatient Department (OPD) with subumbilical abdominal wall defect, absent anterior bladder wall with epispadiasis and was diagnosed as a case of adult classic bladder exstrophy with Epispadiasis complex. There was no history of any fever, haematuria, dysuria or abdominal pain. His ultrasound abdomen and intravenous pyelography reported normal kidney function. He had a low Body Mass Index (BMI) (17.5 kg/m2) with serum creatinine of 0.6 mg/dL. The patient underwent a complete primary repair, including bladder template closure and bladder neck reconstruction using Young-Dees-Leadbetter technique. Epispadias was repaired with the Modified Cantwell-Ransley approach. Abdominal wall defect closure was done with the help of rectus abdominis muscle flap which was later grafted using Split Thickness Skin Graft (STSG). Postoperatively, a small vesicocutaneous fistula developed which healed spontaneously over two weeks period. On follow-up patient was on clean intermittent catheterisation with some incontinence episodes during night-time. Bladder exstrophy in adult patients is rare, as the condition is usually identified in the neonatal period and can be surgically corrected early on. Due to the complexity of the surgery, these cases require thorough multidisciplinary evaluation and careful planning for successful correction.